Biaxial stress concentration of pultruded GFRP perforated plate considering anisotropic factor. (October 2021) - Xiong, Zhihua; Zhao, Chenyu; Liu, Yuqing; Xin, Haohui; Meng, Yang
Abstract: ultruded GFRP perforated plates are widely used in composite bridge and truss. Stress concentration is an inevitable focus of the structural design and analysis. This paper investigated the stress concentration of pultruded perforated plate under both uniaxial and biaxial stress. The hole's radius r, the width w, height h of plate and stack layer were involved. Biaxial stress parametric Finite Element (FE) model of GFRP perforated plates were created. In terms of notch stress in GFRP perforated plate, the stress concentration of 0 degreesply is significant under unidirectional tension. When height to radius ratio is greater than 0.15 (2r/h > 0.15), the stress concentration factor (SCF) is suggested to be modified based on Tan's model. The biaxial status of tension–compression is the governing load combination of GFRP perforated plate. The analysis method of biaxial status has been proposed in the paper. By arranging the layer angle of the non-0° layer of the laminate, the relationship between SCF of perforated plate and the anisotropic factor was found.